Acceptability and implementation of a comprehensive digital diabetes self-management platform (MyWay Diabetes): a qualitative protocol - Martin K Rutter; Hibbah Osei-Kwasi; Joanna Brooks; Tony Willis; Alex Bickerton; Deborah J Wake; Daniel Taylor; Mats Stage Baxter; Rhiannon E Hawkes; Dennis Ashpole (BMJ Open)
Introduction Diabetes is one of the most common long-term health conditions worldwide, placing a huge economic burden on health services. Diabetes self-management education and support programmes can support people with diabetes to manage their condition; however, uptake of face-to-face services remains low. Digital self-management tools are becoming increasingly available. MyWay Diabetes is a digital platform that offers a comprehensive self-management and education programme accessible through a mobile app and website and allows patients to access their personal healthcare records. Following successful implementation in Scotland, MyWay Diabetes is now being rolled out in three geographical areas in England. We plan to undertake three qualitative studies, as part of a larger mixed-methods research programme, to assess whether MyWay Diabetes is acceptable across diverse patient groups and healthcare professionals and gather views of patients who do not currently use the digital service.Methods and analysis We will conduct three online focus group studies. (1) One focus group with healthcare professionals (n=6–10) to understand their perceptions of implementing MyWay Diabetes in their local regions. (2) Up to four focus groups with existing users of MyWay Diabetes (n=24–40) across the three geographical areas in England to explore their acceptability of the platform. (3) Up to three focus groups with people living with diabetes who do not currently use MyWay Diabetes (n=18–30). Data will be collected using online videoconferencing and analysed thematically using template analysis.Ethics and dissemination Ethical approval was granted by South Central – Berkshire Research Ethics Committee (ref: 25/SC/0125) and The University of Manchester Proportionate Research Ethics Committee (ref: 2025-23064-42006). Study results will be disseminated through peer-reviewed journals, conference presentations, MyWay Digital Health platforms and national bodies. The evidence from this broader mixed-methods evaluation will inform decisions for platform improvement and regional and national commissioning across the National Health Service in England.